2015
DOI: 10.1007/s11745-015-4036-6
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Cycloartenol Synthase (CAS) Function in Tobacco BY‐2 Cells

Abstract: Tobacco BY-2 cell suspensions are our preferred model for studying isoprenoid biosynthesis pathways, due to their easy genetic transformation and the efficient absorption of metabolic precursors, intermediates, and/or inhibitors. Using this model system, we have analyzed the effects of chemical and genetic blockage of cycloartenol synthase (CAS, EC 5.4.99.8), an oxidosqualene cyclase that catalyzes the first committed step in the sterol pathway of plants. BY-2 cells were treated with RO 48-8071, a potent inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Mishra et al 29 tried to explore the WsCAS gene function and discovered that RNAi and over-expression of WsCAS can regulate withanolide biosynthesis. Introduction of RO 48-8071 as a CAS inhibitor caused diminished phytosterol synthesis but did not affect triterpenoid accumulation 30 . Therefore, we hypothesize that mogrosides can accumulate significantly by reducing by-pass of SgCAS expression.…”
Section: Discussionmentioning
confidence: 85%
“…Mishra et al 29 tried to explore the WsCAS gene function and discovered that RNAi and over-expression of WsCAS can regulate withanolide biosynthesis. Introduction of RO 48-8071 as a CAS inhibitor caused diminished phytosterol synthesis but did not affect triterpenoid accumulation 30 . Therefore, we hypothesize that mogrosides can accumulate significantly by reducing by-pass of SgCAS expression.…”
Section: Discussionmentioning
confidence: 85%
“…If the photosynthetic membrane system is protected by flavonoids, ascorbate and tocopherols [28,[39][40][41], then cell walls are protected by lignin [38]. Reduced DNA methylation in Pc-Al increases biosynthesis of sterols, tocopherols, flavonoids, isoflavonoids and lignins because these plant metabolites are epigenetically regulated by silencing genes [40,42,43]. Cross-sections through adventitious roots of As 100 and As 250 plants showed the deformation of root cell walls as a result of lignification ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…If the photosynthetic membrane system is protected by flavonoids, ascorbate and tocopherols [28,[39][40][41], then cell walls are protected by lignin [38]. Reduced DNA methylation in Pc-Al increases biosynthesis of sterols, tocopherols, flavonoids, isoflavonoids and lignins because these plant metabolites are epigenetically regulated by silencing genes [40,42,43].Cross-sections through adventitious roots of As 100 and As 250 plants showed the deformation of root cell walls as a result of lignification (Figure 3). Zanella et al [44] observed morphological changes in tobacco roots growing in As and Cd contaminated solutions.…”
Section: Discussionmentioning
confidence: 99%